Influencia del modelo pedagógico por alternancia en el desarrollo local de cinco comunidades rurales del departamento de Petén, Guatemala - Rodriguez Max, Deysi Lisbeth (2021)
This article presents the results of an investigation about the implementation of the by Alternation Pedagogical Model in Petén, Guatemala, whose purpose was to determine the influence of the model on local development. The approach is mixed, not experimental, explanatory, using instruments that allowed the analysis of inferential statistics and the use of ethnographic methods. The sampling design was two-stage, aimed at students, teachers and principals. With the results of the research, it can be affirmed that this model is contributing with human development through the processes of systematic education and training for life in which young people participate, which in the future may become the main actors for the development of the environment rural.